Exploring Importance of Onnlin;e Review on Price - Berger, Paul D.; Chen, Qiuyi; Tang, Jiaye; Furqan, Muhammad (Advances in Social Sciences Research Journal, 2020)
This paper considers the importance of online reviews and their effects on different parameters of a business’ product or service. We use Airbnb as our source of data and tested customer reviews and other variables within the business to determine their influence on Airbnb’s price. We performed our study primarily by using stepwise regression analyses. The results of our analysis are potentially helpful for businesses to develop their marketing and pricing strategies based on how significant variables are. Keywords: Airbnb, number of reviews, overall satisfaction score, stepwise regression analysis, pricing strategy